Congruences in ordered pairs of partitions - Paul Hammond; Richard Lewis (International Journal of Mathematics and Mathematical Sciences)
Dyson defined the rank of a partition (as the first part minus the number of parts) whilst investigating certain congruences in the sequence p−1(n). The rank has been widely studied as have been other statistics, such as the crank. In this paper a birank is defined which relates to ordered pairs of partitions, and is used in an elementary proof of a congruence in p−2(n).